Pathways to culturally sensitive tourism policies and practices - Lüthje, Monika; Höckert, Emily; Kugapi, Outi (Routledge, 2024)
Market-driven development, outsider operators with little knowledge of Indigenous or other local cultures, stereotypical representations and cultural appropriation are common interrelated problems in Arctic tourism. This chapter brings together discussions of social practices and cultural sensitivity in order to gain a better understanding of how more inclusive, legitimate and effective sustainable tourism policies can be formulated. Our research draws on a wide range of stakeholder interviews and benchmarking in Arctic Finland, Sweden, Norway, Greenland and Canada. It focuses on two bundles of culturally sensitive practices that tourism companies utilise, according to our empirical material: reciprocal practices enhancing collaboration and respectful practices related to authenticity. Moreover, we identify local knowledge as the connecting element between these two bundles. This chapter suggests cultural sensitivity as a novel framework for tourism policymaking and sustainable tourism practices.